2018
DOI: 10.1101/483933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expanded genomic analyses for male voice-breaking highlights a shared phenotypic and genetic basis between puberty timing and hair colour

Abstract: The timing of puberty is highly variable and has important consequences for long-term health.Most of our understanding of the genetic control of puberty timing is based on studies in women, as age at menarche is often recorded. Here, we report a multi-trait genome-wide association study for male puberty timing, based on recalled timing of voice breaking and facial hair, with an effective sample size of 205,354 men, nearly four-fold larger than previously reported. We identify 78 independent signals for male pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Puberty is characterized by the reactivation of the hypothalamic–pituitary–gonadal (HPG) axis after childhood leading to physical changes and sexual maturation. The timing of puberty is linked to a number of later health outcomes, such as lifetime incidence of obesity, type 2 diabetes, hypertension and cancer (Day et al ., 2015b; Hollis et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Puberty is characterized by the reactivation of the hypothalamic–pituitary–gonadal (HPG) axis after childhood leading to physical changes and sexual maturation. The timing of puberty is linked to a number of later health outcomes, such as lifetime incidence of obesity, type 2 diabetes, hypertension and cancer (Day et al ., 2015b; Hollis et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We could not find publicly available summary statistics for male pubertal timing. However, Hollis et al [6] tested genetic correlations of male pubertal timing with several of the traits used in this study. The authors also report a genetic correlation of male and female pubertal timing of r g = .683, p<2.6E-213, indicating that genetic correlations of male and female pubertal timing should show substantial agreement.…”
Section: Ethical Approvalmentioning
confidence: 99%
“…MR-studies have demonstrated the causal association of BMI and pubertal timing in both directions, suggesting a causal effect of BMI on pubertal timing and vice versa [4,5]. In a recent paper, a genetic correlation was also found for male pubertal timing and BMI [6].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations